Aurin Tricarboxylic Acid Inhibits Platelet Adhesion to Collagen by Binding to the 509-695 Disulphide Loop of von Willebrand Factor and Competing with Glycoprotein Ib - Girma, J P; Fressinaud, E; Christophe, O; Rouault, C; Obert, B; Takahashi, Y; Meyer, D (Thrombosis and Haemostasis, 1992)
Aurin tricarboxylic acid (ATA) is known to inhibit ristocetin-induced platelet agglutination but not arachidonic acid-, epinephrine- or ADP-induced aggregation. Its capacity to abolish human von Willebrand factor (vWF)-platelet interactions was further investigated by measurement of platelet adhesion to collagen, platelet agglutination tests and binding studies. In flowing blood using parallel-plate perfusion chambers and human collagen, ATA inhibited platelet adhesion to completion in a dose-dependent manner only at the highest shear rate tested (2,600 s–1). It was without effect at 100 and 650 s–1. ATA completely abolished vWF-dependent platelet agglutination induced by ristocetin, botrocetin and asialo-vWF, respectively. 125I-vWF binding to ristocetin- and botrocetin-treated platelets, to heparin and to sulfatides as well as 125I-botrocetin binding to vWF was competitively inhibited by ATA. By contrast, binding of 125I-vWF to collagen was not affected. To further localize the domain of vWF interacting with ATA, experiments of inhibition of binding of selected 125I-monoclonal antibodies (MoAbs) to immobilized vWF by ATA were performed. Our data led to the conclusion that: 1) the interaction of ATA with vWF involves sequences of the A1 disulphide loop of vWF (residues 509–695) and close epitopes which interact with GPIb and 2) the inhibition of platelet adhesion by ATA occurs only at a high shear rate where vWF is known to play a key role. Thus ATA, which blocks the vWF/GPIb pathway by interfering with vWF and not with platelets, is a potential tool in preventing the early stages of thrombosis.